2009
DOI: 10.1177/1352458509351542
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in multiple sclerosis. A comparative population-based study in Nord-Trøndelag County, Norway

Abstract: Anxiety and depression are widely distributed symptoms among multiple sclerosis patients and in the general population. We assessed the prevalence of anxiety and depression in the multiple sclerosis population in Nord-Trøndelag County, Norway compared with Norway's general population. The Hospital Anxiety and Depression Scale questionnaire was completed by 172 MS patients and 56,000 controls. A cut-off of > or =8 was used to define significant symptoms of anxiety and depression. Fatigue was measured using Krup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
84
2
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 39 publications
(42 reference statements)
14
84
2
9
Order By: Relevance
“…The present study shows that persons with MS report symptoms of anxiety (20.2%) in a statistically significantly higher proportion than that in the normal population; these results are in line with other publications, for instance: Beiske, 19.3% [15]; Korostil, 18.6% [16]; Kehler, 25.0% [17]; and Dahl, 30.2% [18]. However, the prevalence of anxiety and its relation to socio-demographic and clinical characteristics of the MS patient population is much less thoroughly investigated than prevalence of depression in the general population and needs much more attention from scientists [19].…”
Section: Discussionsupporting
confidence: 81%
“…The present study shows that persons with MS report symptoms of anxiety (20.2%) in a statistically significantly higher proportion than that in the normal population; these results are in line with other publications, for instance: Beiske, 19.3% [15]; Korostil, 18.6% [16]; Kehler, 25.0% [17]; and Dahl, 30.2% [18]. However, the prevalence of anxiety and its relation to socio-demographic and clinical characteristics of the MS patient population is much less thoroughly investigated than prevalence of depression in the general population and needs much more attention from scientists [19].…”
Section: Discussionsupporting
confidence: 81%
“…A study of 50 MS patients attending an outpatient clinic reported that BDI scores increased with disease severity and physical disability but not with disease duration (15,(27)(28)(29)(30)(31) In this study we found a significant correlation between depression and an objective measure of disability, the EDSS. Separate calculations of the correlation between depression and the 8 functional systems of the EDSS revealed that only bowel and bladder dysfunction and sensitive score were correlated with BDI score.…”
Section: Resultssupporting
confidence: 55%
“…Twenty-three patients showed no symptoms of depression (BDI score 1-10), 4 patients had mild mood disturbance (BDI score 11-16), 3 had borderline clinical depression (BDI score [17][18][19][20], and 2 had moderate depression (BDI score [21][22][23][24][25][26][27][28][29][30]. The mean BDI score was 8.71±7.…”
Section: Resultsmentioning
confidence: 99%
“…These limitations may result in an overestimation of anxiety and depression [15]. Unlike most screening instruments, the Hospital Anxiety and Depression Scale (HADS) [16] was designed to prevent false-positives in somatic conditions; has been validated for medically ill patients and is widely used in MS [15][16][17][18]. The ideal HADS subscales' cut-off points for MS are a matter of debate.…”
Section: Introductionmentioning
confidence: 99%